2006
DOI: 10.1038/sj.jhh.1002057
|View full text |Cite
|
Sign up to set email alerts
|

NAD(P)H oxidase p22phox gene C242T polymorphism, nitric oxide production, salt sensitivity and cardiovascular risk factors in Hispanics

Abstract: Mutations in the NAD(P)H oxidase gene may be associated with abnormal superoxide generation, nitric oxide (NO) availability and cardiovascular diseases. We investigated the prevalence of the NAD(P)H oxidase p22phox gene C242T polymorphism, and its possible association with blood pressure, NO production, salt sensitivity and cardiovascular risk factors in Hispanics. Genotype frequencies were as follows: CC, 52.9%; CT, 40.3%; and TT, 6.8%. There were no significant differences in systolic blood pressure, diastol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 40 publications
(79 reference statements)
4
14
0
1
Order By: Relevance
“…Castejón et al (12) reported lower nitric oxide (NO) metabolites levels in individuals with the TT genotype, and they concluded that increased NADPH oxidase-dependent superoxide production could affect NO bioactivity. Kals et al (31) showed the relationship between high-grade oxidative stress and increased arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Castejón et al (12) reported lower nitric oxide (NO) metabolites levels in individuals with the TT genotype, and they concluded that increased NADPH oxidase-dependent superoxide production could affect NO bioactivity. Kals et al (31) showed the relationship between high-grade oxidative stress and increased arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, an impaired NAD(P)H oxidase activity has been linked to enhanced generation of cytotoxic NO derivates (e.g. peroxynitrite), abnormal pressor responses [11] , enhanced salt sensitivity [12] and a procoagulant state [13] as well as postinfarction inflammation and hypercholesterolemia [14] . From our experience of performing genotype analysis in a typical population of elderly stroke patients, we note that in older subjects weak associations are more likely to be masked by the high prevalence of conventional vascular risk factors than in a population of juvenile patients with a lower burden of risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…One study also reports equal risk for cardiovascular risk factors, but increased salt sensitivity and decreased levels of nitric oxide metabolites in His72Tyr carriers (129).…”
Section: Subunits and Regulatory Proteinsmentioning
confidence: 99%